2015
DOI: 10.1200/jop.2014.001536
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Interprofessional Teamwork in Inpatient Medical Oncology Units

Abstract: In inpatient oncology units, discrepancies exist between nurses' and physicians' ratings of teamwork and collaboration. Oncologists seem to be unaware that teamwork is suboptimal in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…Previous research used the SAQ to evaluate attitudes among intensive care units, nursing and residential homes, pharmacies, medical oncology units, the operating room and the neonatal intensive care unit. 9,12-17 The general finding of these studies is that the SAQ is a valid tool with good internal consistency. In the current study, Cronbach’s α for the different dimensions ranged from .72 to .89, confirming these findings from previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research used the SAQ to evaluate attitudes among intensive care units, nursing and residential homes, pharmacies, medical oncology units, the operating room and the neonatal intensive care unit. 9,12-17 The general finding of these studies is that the SAQ is a valid tool with good internal consistency. In the current study, Cronbach’s α for the different dimensions ranged from .72 to .89, confirming these findings from previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Developing such a shared mental model requires intentional effort and planning, which includes open communication and coordination within the oncology team. This point is critical because communication lapses between physicians and nurses are major barriers to all forms of collaboration within oncology teams . Some teams might struggle to reach a consensus opinion about the best approach to prognostic communication.…”
Section: Shared Mental Modelmentioning
confidence: 99%
“…If the nurse is not involved in these conversations, he or she may not know exactly what was discussed with the family, making it difficult to interact with the family and potentially limiting the nurse's ability to function commensurate with his/her position. In previous studies, nurses have identified negative attitudes toward the importance of communication as one of the primary barriers to collaboration (Weaver et al, 2015). Findings from this study suggest that nurses who have more collaborative relationships with their physician colleagues have better experiences with prognosis-related communication and less moral distress.…”
Section: Implications For Vulnerable Populationsmentioning
confidence: 65%
“…Such activity results in a "logic of collaboration rather than a logic of competition" (D'Amour et la., 2005, p. 117 (Larson, 1999). Weaver, Callaghan, Brandman, and O'Leary (2015) surveyed nurses, residents, hospitalists, and oncology physicians to characterize the perceptions of teamwork in the inpatient oncology setting. They also explored barriers to establishing strong collaboration between nurses and physicians.…”
Section: Figure 2 Theoretical Modelmentioning
confidence: 99%